Multi-factor models and signal processing techniques : application to quantitative finance - Darolles, Serge; Duvaut, Patrick; Jay, Emmanuelle (Hoboken : Wiley ; London : ISTE, 2013)
With recent outbreaks of multiple large-scale financial crises, amplified by interconnected risk sources, a new paradigm of fund management has emerged. This new paradigm leverages "embedded" quantitative processes and methods to provide more transparent, adaptive, reliable and easily implemented "risk assessment-based" practices. This book surveys the most widely used factor models employed within the field of financial asset pricing. Through the concrete application of evaluating risks in the hedge fund industry, the authors demonstrate that signal processing techniques are an intere.
Factor Models and General Definition / Serge Darolles, Patrick Duvaut, Emmanuelle Jay -- Factor Selection / Serge Darolles, Patrick Duvaut, Emmanuelle Jay -- Least Squares Estimation (LSE) and Kalman Filtering (KF) for Factor Modeling: / Serge Darolles, Patrick Duvaut, Emmanuelle Jay -- A Regularized Kalman Filter (rgKF) for Spiky Data / Serge Darolles, Patrick Duvaut, Emmanuelle Jay -- Some Probability Densities -- Supplemental Images.
Includes bibliographical references and index (pages 143-152).
Online resource; title from PDF title page (Wiley, viewed Aug. 14, 2013).
Keywords: Factor analysis; Signal processing -- Mathematics; Factor analysis; Signal processing -- Mathematics; Wireless communication systems; Factor analysis; Signal processing -- Mathematics; Electronic books